1995
DOI: 10.1111/j.1558-5646.1995.tb02319.x
|View full text |Cite
|
Sign up to set email alerts
|

EVOLUTIONARY ORIGIN OF A PARTHENOFORM, THE AMAZON MOLLYPOECILIA FORMOSA, ON THE BASIS OF A MOLECULAR GENEALOGY

Abstract: Abstract.-The appearance of vertebrate species that reproduce without genetic recombination has been explained by their origin from a rare hybridization event between members of two distantly related species. For the first recognized vertebrate unisexual, the Amazon molly Poeciliaformosa, mostly morphological and biochemical genetic information has been available so far with respect to its evolutionary origin. DNA sequence analyses of transcribed portions of the genome (tyrosine kinase proto-oncogenes) demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 34 publications
3
58
0
Order By: Relevance
“…However, most of unisexual vertebrates, such as kleptogenetic Ambystoma salamanders (Bi and Bogart, 2010;Spolsky et al, 1992), hybridogenetic Poeciliopsis fish (Quattro et al, 1992), gynogenetic Amazon molly (Lampert and Schartl, 2008;Schartl et al, 1995), Phoxinus eosneogaeus hybrids (Angers and Schlosser, 2007), and gynogenetic Cobitis (Janko et al, 2003), have been revealed to have long history and large ranges of geographical distribution (Avise, 2008). And, high genetic diversity has been extensively observed in gynogenetic or hybridogenetic fish (Angers and Schlosser, 2007;Cunha et al, 2011;Schmidt et al, 2011;Stöck et al, 2012), kleptogenetic amphibians (Bi and Bogart, 2010) and parthenogenetic reptiles (Fujita et al, 2007;Kupriyanova, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, most of unisexual vertebrates, such as kleptogenetic Ambystoma salamanders (Bi and Bogart, 2010;Spolsky et al, 1992), hybridogenetic Poeciliopsis fish (Quattro et al, 1992), gynogenetic Amazon molly (Lampert and Schartl, 2008;Schartl et al, 1995), Phoxinus eosneogaeus hybrids (Angers and Schlosser, 2007), and gynogenetic Cobitis (Janko et al, 2003), have been revealed to have long history and large ranges of geographical distribution (Avise, 2008). And, high genetic diversity has been extensively observed in gynogenetic or hybridogenetic fish (Angers and Schlosser, 2007;Cunha et al, 2011;Schmidt et al, 2011;Stöck et al, 2012), kleptogenetic amphibians (Bi and Bogart, 2010) and parthenogenetic reptiles (Fujita et al, 2007;Kupriyanova, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In Mexico P. formosa generally live in the same habitat and in mixed shoals with P. mexicana, and in Texas with P. latipinna. Poecilia mexicana is known to be the maternal ancestor of this hybrid (Avise et al 1991), and recent research (Schartl et al 1995b) shows that either an unknown population of P. latipinna or an extinct form from the P. latipinna ancestry was the paternal form. This group has received considerable interest from evolutionary biologists because the maintenance of this mating complex depends upon mixed-species associations and mating between heterospecifics.…”
mentioning
confidence: 99%
“…The Amazon molly, Poecilia formosa (Girard 1859), is an all-female species of fish of hybrid origin (Hubbs & Hubbs 1932;Schartl et al 1995b) which relies on insemination with sperm from males of closely related sexual species (Turner 1982;Balsano et al 1989). It reproduces by gynogenesis, that is the sperm normally only trigger embryogenesis without a genetic contribution (but see Schartl et al 1995a).…”
mentioning
confidence: 99%
“…As summarized by Schlupp et al (2002;also see Darnell & Abramoff 1968, Schartl et al 1995, the hybridization event between P. mexicana and P. latipinna that gave rise to P. formosa occurred 100,000 year ago in the Rio Tampico in northeastern Mexico. It is not known, however, if sailfin and Amazon mollies spread northward from Mexico together, of if sailfins already occupied their current range prior to the existence of Amazons, who then spread northward after their founding hybridization in northern Mexico.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that behavior has changed faster than allozymes. This may be a result of strong selective pressures from the parasitic unisexual Amazon mollies starting about 100,000 years ago (Avise et al 1991, Schartl et al 1995) that has consequently resulted in reproductive character displacement in male mating preferences between sympatric and allopatric populations (Ryan et al 1996a, Gabor & Ryan 2001 …”
Section: Discussionmentioning
confidence: 99%